Congenital Radioulnar Synostosis Review: Recommendations and Treatment Outcomes - Sergi Alabau-Rodriguez; Jose Felix Garrido Ferrer; Xavier Bulló Mir; Lidia Ana Martín Dominguez; Albert Pardo Pol; Francisco Soldado Carrera (MDPI AG, 2024)
Background/Objectives: Congenital radioulnar synostosis (CRS) is a rare congenital disorder of the elbow joint caused by the abnormal fusion of the radius and ulna during fetal development, leading to limited forearm rotation and functional impairment. This narrative review aims to summarize the key aspects of diagnostic suspicion, treatment options, and lifestyle management strategies for individuals affected by CRS. Relevant sections: While CRS often occurs sporadically, there are familial cases with an autosomal dominant inheritance pattern. The diagnosis is established through a combination of clinical evaluation and radiological imaging, which confirms the presence and extent of the synostosis. Identifying the specific type and severity of CRS is critical for management decisions. Surgical interventions are considered based on factors such as the patient's age, level of functional limitation, and symptom severity, while conservative treatment may be appropriate for cases with mild impairment. Discussion: Various surgical techniques have been described, but derotation osteotomy has emerged as a preferred option due to its predictable improvement in forearm function. Nevertheless, surgical treatment poses challenges, including potential complications like nerve injury and recurrence of deformity. Cultural and individual considerations, such as the desired forearm position, must be addressed to achieve optimal outcomes aligned with the patient's lifestyle and needs. Conclusions: Managing CRS requires a nuanced and individualized approach, recognizing the unique challenges each patient presents. This review highlights the importance of continuous research to refine diagnostic and therapeutic strategies, ultimately aiming to enhance functional outcomes and quality of life for CRS patients.